1982
DOI: 10.1111/j.1744-6570.1982.tb02187.x
|View full text |Cite
|
Sign up to set email alerts
|

Job Orientation of Black and White College Graduates in Business

Abstract: Differences in job orientation between black and white male and female business college graduates were examined. Significant race differences were found on 10 of 25 job characteristics, with blacks rating 9 of these more important than whites. Significant race by sex interactions exist on four characteristics, while sex differences were found on nine. Factor analysis indicates that blacks value long-range career objectives and structure considerably more than do whites, while their preference for intrinsic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 20 publications
4
29
1
Order By: Relevance
“…While classification and credit hours were both significant, race remained highly significant at p = .001. Brenner and Tomkiewicz (1982) in which African-Americans scored higher on almost all values tested. To the extent that values reflect objectives a person seeks to obtain in his or her career, this result suggests that African-American respondents desire more from a career than Caucasian respondents.…”
Section: Hypothesis Twomentioning
confidence: 94%
See 1 more Smart Citation
“…While classification and credit hours were both significant, race remained highly significant at p = .001. Brenner and Tomkiewicz (1982) in which African-Americans scored higher on almost all values tested. To the extent that values reflect objectives a person seeks to obtain in his or her career, this result suggests that African-American respondents desire more from a career than Caucasian respondents.…”
Section: Hypothesis Twomentioning
confidence: 94%
“…Two published studies have specifically examined differences in work-related values between African-Americans and other races. Brenner and Tomkiewicz (1982) surveyed African-American and Caucasian business students and found that African-Americans scored higher on many job values. They interpreted this finding as suggesting that African-Americans wanted more from a job than Caucasians.…”
Section: Outcome Expectations and African-american Studentsmentioning
confidence: 99%
“…Twenty-one statements about work goals were derived from Manhardt's (1972) classic work values scale and slightly changed (Brenner and Tomkiewicz, 1982;Bu and McKeen, 2001). The survey was designed to measure job orientation of the business students from the USA and China.…”
Section: Methodsmentioning
confidence: 99%
“…Brennen and Blazini (1988) as well as Brennen and Tomkiewicz (1982) reported that African Americans in work settings tend to value independence more than doWhites.This emphasis on independence at work has also been linked to African American managers placing value on asserting themselves on the job (Milbourn & Cuba, 1980). These differences in communicative behaviors and values may result from what Bell and Nkomo (2001) referred to as separate paths.…”
mentioning
confidence: 95%